The Argumentative turn in policy analysis and planning - Fischer, Frank, 1942-; Forester, John, 1948- (e-Duke books scholarly collection., 1993)
A work from leading planners and policy analysts, representing practical, theoretical and political advances in the field of planning, public administration and public policy.